Fabrication of Fe3O4@Au hollow spheres with recyclable and efficient catalytic properties. (30th November 2015) - Xia, Qingdong; Fu, Shanshan; Ren, Guojuan; Chai, Fang; Jiang, Jingjie; Qu, Fengyu
Abstract : A view of the preparation process and the evaluation of the catalysis activity of Fe3 O4 @Au hollow spheres. Abstract : The preparation of catalysts with superior catalytic activity, reusability and economical processes is highly desirable. In this work, we report a route for the facile synthesis of Fe3 O4 @Au hollow spheres. The Fe3 O4 @Au hollow spheres were prepared based on Fe3 O4 hollow spheres with gold nanoparticles inlaid on their surface. The Fe3 O4 @Au hollow nanospheres were characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), transmission electron microscopy (TEM) and scanning electron microscopy (SEM) with energy-dispersive X-ray spectroscopy (EDX). The Fe3 O4 @Au hollow spheres exhibit remarkable catalytic activity and good reusability toward the reduction of 4-nitrophenol and potassium hexacyanoferrate(iii ) by NaBH4 in water. In addition, the catalysts show good reusability for at least 6 successive cycles.